Seven Guiding Principles for Building Fellowship in SoTL - Anita Acai; Mandy Frake; Melanie Hamilton; Patrick Maher; Roselynn Verwoord; Cherie Woolmer (Canadian Journal for the Scholarship of Teaching and Learning)
Considering the expansive context of the international Scholarship of Teaching and Learning (SoTL) community, SoTL scholars may wish to reflect and identify what exists for building and nurturing fellowship, and how they may be enacted in practice to benefit others. In this reflective article, we draw on our experiences as International Society for the Scholarship of Teaching and Learning (ISSOTL) Fellows to offer seven guiding principles for building fellowship. These principles include: (1) create space, (2) avoid and resist formal roles, (3) maintain confidentiality and build trust, (4) allow members to self-determine their level of engagement, (5) embrace a group process that is emergent and organic, (6) find congruence in values, and (7) acknowledge the evolutionary nature of the collective. When considered as a meaningful process of community building and engagement, these principles may be useful points of discussion, reflection, and as Felten (2013) states in relation to his Principles for Good Practices in SoTL, to “...articulate a vision of scholarship that enhances, perhaps even transforms, teaching and learning in higher education” (p. 121). Much like Felten, our objective was not to craft a detailed, step-by-step guide for fellowship. Instead, we have provided a series of reference points intended to help people clarify and demystify their own SoTL communities and networks, whether these communities are formal or informal in nature.